2012
DOI: 10.1111/j.1365-2796.2012.02552.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐type natriuretic peptide in the evaluation and management of dyspnoea in primary care

Abstract: land). B-type natriuretic peptide in the evaluation and management of dyspnoea in primary care. J Intern Med 2012; 272:504-513.Objectives. The rapid and accurate diagnosis of heart failure in primary care is a major unmet clinical need. We evaluated the additional use of B-type natriuretic peptide (BNP) levels. Design. A randomized controlled trial.Setting. Twenty-nine primary care physicians in Switzerland and Germany coordinated by the University Hospital Basel, Switzerland.Subjects. A total of 323 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…The three papers 265,288,289 examining other (non-spirometry) technologies suggested that POC testing can have a positive impact on GP differential diagnosis, diagnostic certainty and time to treatment, although the impact on specialist referral is less clear. A simple algorithm for asthma also may be a useful decision-aid.…”
Section: Summary Of Evidence From Intervention Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The three papers 265,288,289 examining other (non-spirometry) technologies suggested that POC testing can have a positive impact on GP differential diagnosis, diagnostic certainty and time to treatment, although the impact on specialist referral is less clear. A simple algorithm for asthma also may be a useful decision-aid.…”
Section: Summary Of Evidence From Intervention Studiesmentioning
confidence: 99%
“…All but three 265,284,288 of these examined the use of spirometry by primary care staff. The papers considered the potential value of spirometry during a consultation, the accuracy of spirometry carried out in primary care, and whether or not training courses could enhance the quality of spirometry.…”
Section: Additional Diagnostic Technology/information In the General mentioning
confidence: 99%
See 3 more Smart Citations